Melamine and phenolic aldehyde composite resin-based hard carbon microspheres as well as preparation method and application thereof

By preparing melamine and phenolic composite resin-based hard carbon microspheres, the problems of poor rate performance and low compaction density of hard carbon materials were solved, achieving high energy density and excellent cycle performance, making them suitable for industrial production.

CN121672486APending Publication Date: 2026-03-17WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512016115.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing hard carbon materials have poor rate performance and low compaction density, making them difficult to mass-produce industrially, and sodium-ion batteries have insufficient energy density.

Method used

A method for preparing melamine and phenolic composite resin-based hard carbon microspheres was adopted. By introducing melamine resin and phenolic resin into the resin precursor to form a molecular-level nitrogen element dispersion, a dense three-dimensional cross-linked network structure was constructed to prepare spherical hard carbon microspheres.

Benefits of technology

The improved electronic conductivity and sodium ion adsorption capacity of hard carbon materials enhance the energy density and rate performance of sodium-ion batteries, making them suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672486A_ABST
    Figure CN121672486A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to melamine and phenolic aldehyde composite resin-based hard carbon microspheres as well as a preparation method and application thereof. The preparation method comprises the following steps: taking phenols, melamine and aldehydes as raw materials, obtaining melamine and phenolic aldehyde composite resin microspheres under the action of a dispersing agent and a catalyst, and then performing a low-temperature and high-temperature carbonization process to finally obtain the melamine and phenolic aldehyde composite resin-based hard carbon microsphere material. According to the present invention, the cost is low, the preparation is simple, the hard carbon negative electrode has advantages of excellent rate performance, high capacity, high energy density and good cycle life, and in addition, due to the special spherical structure, the material further has high compaction density, and is very suitable for industrial large-scale promotion. The hard carbon microsphere negative electrode material disclosed by the invention is used for a sodium ion battery, the first reversible gram capacity reaches 335mAh / g, and the hard carbon microsphere negative electrode material has excellent rate capability and still has 67% of capacity retention ratio under the current density of 10C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy materials technology, and in particular relates to a melamine and phenolic composite resin-based hard carbon microsphere, its preparation method, and its application in sodium-ion batteries. Background Technology

[0002] In recent years, lithium-ion batteries have seen rapid development in electric vehicles and energy storage due to their superior performance. However, the uneven distribution of lithium elements hinders their further development. Sodium, on the other hand, has advantages such as low cost and abundant reserves. Furthermore, it belongs to the same group as lithium and possesses similar physical / chemical properties, showing great promise for future commercialization.

[0003] Currently, hard carbon is mainly used as the energy storage material in sodium-ion batteries. Hard carbon can be further classified according to its source: biomass hard carbon, resin-based hard carbon, and coal-based hard carbon. Resin-based hard carbon is considered the most promising hard carbon material for large-scale production due to the controllable structure and morphology of its precursors. Among the precursors for resin-based hard carbon, phenolic resin is considered the most suitable for industrial production of hard carbon materials due to its low cost and simple processing.

[0004] Many manufacturers have achieved large-scale production of hard carbon fiber, but the inherent weakness of hard carbon materials in terms of electrical conductivity makes rate performance a bottleneck. Current methods to improve the rate performance of hard carbon fiber mainly include heteroelement doping, surface coating, and pore structure design. Among these, heteroelement doping can improve the electronic conductivity of the material and also act as adsorption sites for sodium ions, thus becoming a widely researched area.

[0005] Furthermore, although hard carbon products are already in mass production, most are biomass hard carbon products with irregular blocky morphology. This results in a large number of gaps between microparticles during stacking, which affects the overall compaction density of the hard carbon material. A lower compaction density will affect the energy density of the battery cell, which does not meet the requirements of large-scale industrialization. Resin-based hard carbon, on the other hand, has controllable structure and morphology, and the spherical morphology is more compact than the blocky morphology. Therefore, spherical resin-based hard carbon has become the easiest way to improve the energy density of sodium battery anodes and achieve large-scale industrialization.

[0006] CN115249799A uses hard carbon powder mixed with nitrogen source powders such as urea and melamine for secondary carbonization to obtain nitrogen-doped hard carbon, but the hard carbon powder and nitrogen source powder cannot be fully mixed at the molecular level; CN119430132A uses carbon nanotubes dispersed in a resin precursor, followed by carbonization to obtain resin-based hard carbon material, but the cost of carbon nanotubes is too high, making it difficult to achieve industrial production; CN119284876A also uses melamine as an additive to participate in the reaction of phenolic resin, but the final hard carbon material is in a blocky state, which has a significant impact on the compaction density of hard carbon and the energy density of the battery cell, making it difficult to achieve industrialization.

[0007] Therefore, providing a nitrogen doping method suitable for industrial application is currently a technical challenge in the field of hard carbon. Summary of the Invention

[0008] The purpose of this invention is to address the shortcomings of poor rate performance of current hard carbon materials by providing a method for preparing melamine and phenolic composite resin-based hard carbon microspheres. The melamine resin component achieves molecular-level nitrogen dispersion in the precursor, while the melamine and phenolic resins simultaneously provide a dense three-dimensional cross-linked network structure, ensuring the residual carbon content of the precursor. Furthermore, the morphology of the hard carbon microspheres can also increase the compaction density of the hard carbon material, thereby improving the energy density of the battery.

[0009] Another object of the present invention is to provide such melamine and phenolic composite resin-based hard carbon microspheres and their applications. The hard carbon microsphere material, used as the anode material in sodium-ion batteries, exhibits excellent rate performance, high energy density, and good cycle performance, making it highly suitable for industrial production.

[0010] To achieve the above objectives, the technical solution of the present invention is as follows:

[0011] A method for preparing melamine and phenolic composite resin-based hard carbon microspheres includes the following steps:

[0012] 1) After thoroughly mixing the aldehyde source, dispersant, catalyst, and water, mixed solution A is obtained; after thoroughly mixing the phenol source, melamine, and water, mixed solution B is obtained.

[0013] 2) Add mixed solution A to the reaction vessel, turn on stirring and heating, and then add mixed solution B dropwise to mixed solution A;

[0014] 3) After the addition is complete, heat the mixture to react. After the reaction is complete, cool the mixture and discharge it for filtration, washing, and drying to obtain melamine and phenolic composite resin.

[0015] 4) The obtained melamine and phenolic composite resin is carbonized to obtain hard carbon microsphere material.

[0016] In one specific implementation, the aldehyde source in step 1) is selected from one or more of formaldehyde, acetaldehyde, glutaraldehyde, and furfural.

[0017] In one specific implementation, the dispersant in step 1) is one or more of sodium dodecylbenzene sulfonate, sodium lignosulfonate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether (AEO), polyoxyethylene polyoxypropylene block copolymer, and polysorbate (Tween series).

[0018] In one specific implementation, the phenol source in step 1) is one or more of resorcinol, phloroglucinol, hydroquinone, catechol, p-aminophenol, m-aminophenol, and o-aminophenol.

[0019] In one specific implementation, the catalyst in step 1) is one or more of ammonia, triethanolamine, sodium hydroxide, potassium hydroxide, and sodium carbonate.

[0020] In one specific implementation, the aldehyde source: phenol source: melamine in step 1) is fed in a molar ratio of 1.5-3:1:0.3-0.7, and more preferably, the molar ratio of aldehyde source: phenol source: melamine is 1.8-2.2:1:0.4-0.6.

[0021] In one specific implementation, the mass ratio of the catalyst to the phenol source in step 1) is 1-10:100; more preferably, the mass ratio of the catalyst to the phenol source is 3-7:100.

[0022] In one specific implementation, the mass ratio of the dispersant to the phenol source in step 1) is 1-20:100; more preferably, the mass ratio of the dispersant to the phenol source is 5-10:100.

[0023] In one specific implementation, the solid content of both mixed solution A and mixed solution B in step 1) is adjusted to 10%-40% using water, with the preferred solid content of the mixed solution being 20%-30%.

[0024] In one specific implementation, the stirring speed in step 2) is 300-800 rpm and the heating temperature is 50-80℃.

[0025] In one specific implementation, in step 2), after heating and stirring for 30-90 minutes, the mixed solution B is added dropwise to the mixed solution A, and the dropwise addition rate is 30-90 drops / min.

[0026] In one specific implementation, the reaction temperature of the heating reaction in step 2) is 60-90℃, and the reaction time is 1-8h.

[0027] In one specific implementation, in step 4), the obtained melamine and phenolic composite resin is pulverized and then carbonized in a tube furnace under an inert gas atmosphere. The pulverization method includes one of gyratory crusher, ball mill, air jet mill, and mechanical mill. After pulverization, the resin is sieved with a sieve mesh size of 150 mesh.

[0028] In one specific implementation, the inert gas in step 4) is one of nitrogen, argon, or helium.

[0029] In one specific implementation, the carbonization process in step 4) is as follows: heating to 1000-1600℃ at a heating rate of 2-10℃ / min and holding for 2-8 hours to obtain melamine and phenolic composite resin-based hard carbon microspheres.

[0030] On the other hand, the present invention provides a melamine and phenolic composite resin-based hard carbon microsphere prepared by the aforementioned preparation method.

[0031] In another aspect, the present invention provides an application of melamine and phenolic composite resin-based hard carbon microspheres in the negative electrode of a sodium-ion battery, wherein the battery negative electrode sheet containing melamine and phenolic composite resin-based hard carbon microspheres is prepared by mixing hard carbon microspheres with a conductive agent and a binder and then coating them onto a current collector.

[0032] In one specific implementation, the conductive agent is one or more of acetylene black, Ketjen black, and Super P; the binder is one or more of carboxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, and polyacrylic acid.

[0033] In another aspect, the present invention provides a negative electrode sheet for a sodium-ion battery, the negative electrode sheet comprising a current collector, a conductive additive, a binder, and a hard carbon negative electrode material; wherein the hard carbon negative electrode material is melamine and phenolic composite resin-based hard carbon microspheres prepared by the aforementioned preparation method.

[0034] The present invention also provides a sodium-ion battery, wherein the sodium-ion battery includes the negative electrode sheet of the aforementioned sodium-ion battery.

[0035] The melamine and phenolic composite resin-based hard carbon microspheres of the present invention have the following advantages compared with conventional resin-based hard carbon:

[0036] 1) This invention introduces a large amount of nitrogen element from the source, namely the synthesis of resin precursor. On the one hand, the introduction of nitrogen element can improve electronic conductivity. On the other hand, the introduction of nitrogen element can serve as an adsorption site for sodium ions, thereby increasing capacity.

[0037] 2) While introducing nitrogen, this invention maintains the regular spherical morphology of the precursor, thereby obtaining resin-based hard carbon microspheres. The microsphere morphology can achieve close packing, thereby increasing the compaction density of the hard carbon material and thus improving the energy density of sodium-ion batteries.

[0038] 3) The resin precursor prepared by the present invention has a dual three-dimensional network cross-linked structure of melamine resin and phenolic resin, thus ensuring that the precursor has a high carbonization yield during carbonization.

[0039] 4) The melamine and phenolic composite resin-based hard carbon material of the present invention has the advantages of high carbonization yield, excellent rate performance and high energy density. It has low preparation cost and simple process. Moreover, the prepared spherical resin-based hard carbon has high compaction density, which is very suitable for large-scale industrial production. Attached Figure Description

[0040] Figure 1 This is a scanning electron microscope image of the hard carbon anode material in Example 4 of the present invention. Detailed Implementation

[0041] The present invention will be further illustrated below with specific embodiments. These embodiments are merely illustrative and do not limit the scope of the invention.

[0042] The main raw materials involved in the following examples are all commercially available conventional raw materials, and there are no special restrictions.

[0043]

Example 1

[0044] 1) Mix 3 mol of formaldehyde (aldehyde source), sodium dodecylbenzenesulfonate (dispersant, mass ratio of 5% of phenol source), ammonia (catalyst, mass ratio of 5% of phenol source) with water, and adjust the solid content to 20% to obtain mixed solution A.

[0045] 2) Mix 1 mol of resorcinol (phenol source) and 0.5 mol of melamine with water, and adjust the solid content to 20% to obtain mixed solution B.

[0046] 3) Add A to the reactor and stir at 60°C and 500 rpm for 50 min. Then add B dropwise to A at a rate of 60 drops / min.

[0047] 4) After the addition is complete, the temperature is raised to 60℃ and the reaction is carried out for 8 hours. After cooling, the mixture is filtered, washed, and dried to obtain melamine and phenolic composite resin microspheres.

[0048] 5) The resin microspheres were ball-milled and passed through a 150-mesh sieve. The temperature was increased to 1200℃ at 5℃ / min under a nitrogen atmosphere and held for 4 hours to obtain hard carbon microsphere material.

[0049]

Example 2

[0050] 1) Mix formaldehyde and furfural (phenol source, molar ratio 1:1), total amount 2.0 mol, sodium lignosulfonate (dispersant, mass ratio of 10% of phenol source), sodium hydroxide (catalyst, mass ratio of 7% of phenol source) with water, and adjust the solid content to 30% to obtain mixed solution A.

[0051] 2) Mix 1 mol of phloroglucinol (phenol source) and 0.5 mol of melamine with water, and adjust the solid content to 30% to obtain mixed solution B.

[0052] 3) Add A to the reactor and stir at 70°C and 600 rpm for 30 min. Then add B dropwise to A at a rate of 50 drops / min.

[0053] 4) After the addition is complete, the temperature is raised to 70℃ and the reaction is carried out for 6 hours. After cooling, the mixture is filtered, washed, and dried to obtain melamine and phenolic composite resin microspheres.

[0054] 5) The resin microspheres were ball-milled and passed through a 150-mesh sieve. The temperature was increased to 1400℃ at 8℃ / min under a nitrogen atmosphere and held for 6 hours to obtain hard carbon microsphere material.

[0055]

Example 3

[0056] 1) Mix 1.5 mol of glutaraldehyde (aldehyde source), Tween-80 (dispersant, mass ratio of 20% of phenol source), triethanolamine (catalyst, mass ratio of 1% of phenol source) with water, and adjust the solid content to 40% to obtain mixed solution A.

[0057] 2) Mix 1 mol of hydroquinone (phenol source) and 0.5 mol of melamine with water, and adjust the solid content to 40% to obtain mixed solution B.

[0058] 3) Add A to the reactor and stir at 80°C and 800 rpm for 70 min. Then add B dropwise to A at a rate of 40 drops / min.

[0059] 4) After the addition is complete, the temperature is raised to 80℃ and the reaction is carried out for 4 hours. After cooling, the mixture is filtered, washed, and dried to obtain melamine and phenolic composite resin microspheres.

[0060] 5) The resin microspheres were ball-milled and passed through a 150-mesh sieve. The temperature was increased to 1600℃ at 10℃ / min under a nitrogen atmosphere and held for 2 hours to obtain hard carbon microsphere material.

[0061]

Example 4

[0062] 1) Mix 2.5 mol of formaldehyde (aldehyde source), AEO-9 (dispersant, mass ratio of 3% of phenol source), sodium carbonate (catalyst, mass ratio of 10% of phenol source) with water, and adjust the solid content to 10% to obtain mixed solution A.

[0063] 2) Mix 1 mol of m-aminophenol (phenol source) and 0.5 mol of melamine with water, and adjust the solid content to 20% to obtain mixed solution B.

[0064] 3) Add A to the reactor and stir at 50°C and 300 rpm for 90 min. Then add B dropwise to A at a rate of 90 drops / min.

[0065] 4) After the addition is complete, the temperature is raised to 90℃ and the reaction is carried out for 2 hours. After cooling, the mixture is filtered, washed, and dried to obtain melamine and phenolic composite resin microspheres.

[0066] 5) The resin microspheres were ball-milled and passed through a 150-mesh sieve. The temperature was increased to 1000℃ at 2℃ / min under a nitrogen atmosphere and held for 8 hours to obtain hard carbon microsphere material.

[0067] Comparative Example 1

[0068] Hard carbon microspheres were prepared using the same formulation and method as in Example 4, except that the addition of melamine was omitted in the preparation of mixed solution B in the second step, while the rest of the synthesis and carbonization conditions were the same as in Example 4.

[0069] Comparative Example 2

[0070] Hard carbon microspheres were prepared using a formula and method that were essentially the same as in Example 4. The only difference was that after the phenolic resin was prepared according to the synthesis method in Example 4, the phenolic resin microspheres and melamine powder were uniformly mixed at a mass ratio of 10:1, and the mixture was further carbonized under the same conditions as in Example 4.

[0071] Comparative Example 3

[0072] Hard carbon anode material was prepared according to the preparation method in Example 1 of CN 119284876 A.

[0073] 1) Heat 1 mol of phenol to 60℃ to melt it into a liquid state, and stir it evenly with 0.1 mol of asparagine to obtain mixture A.

[0074] 2) Disperse 2 mol of formaldehyde in 20 mol of water, heat to 60°C, then add 0.5 mol of melamine and 0.05 mol of tetrapropylammonium hydroxide in sequence, stir to dissolve, and stir evenly to obtain mixture B.

[0075] 3) Add the mixture B prepared in step (2) to the mixture A obtained in step (1), keep heating and stir evenly to obtain mixture C.

[0076] 4) Transfer the mixture C prepared in step (3) to the reactor and treat it at 90°C for 3 hours.

[0077] 5) After drying the sample prepared in step (4), heat it to 600℃ at a heating rate of 5℃ / min in an argon atmosphere and hold it for 2 hours. After grinding the prepared sample, heat it to 600℃ at a heating rate of 10℃ / min in an argon atmosphere, and then heat it to 1400℃ at a heating rate of 2℃ / min and hold it for 4 hours.

[0078] The hard carbon microspheres prepared using Examples 1-4 and Comparative Examples 1-3 were subjected to electrochemical performance tests (following national standard GB / T 44027.1-2024), nitrogen content tests (following industry standard NB / SH / T0656-2017), SEM (scanning electron microscopy) tests (following national standard GB / T 46057-2025), and compaction density tests (following national standard GB / T 44330-2024). The test results are shown in Table 1.

[0079] Table 1. Test results of hard carbon anode materials in Examples 1-4 and Comparative Examples 1-3

[0080]

[0081] As shown in the table above, the melamine and phenolic composite resin-based hard carbon microspheres prepared by this invention have a high nitrogen doping content, and the prepared hard carbon microspheres are regular spherical in shape, such as... Figure 1 As shown, it has a higher powder compaction density, resulting in higher specific capacity and current capacity retention.

[0082] The above description is merely a basic explanation of the concept of this invention, and any equivalent modifications made based on the technical solution of this invention shall fall within the protection scope of this invention.

Claims

1. A method for preparing melamine and phenolic composite resin-based hard carbon microspheres, characterized in that, The method comprises the following steps: 1) mixing an aldehyde source, a dispersing agent, a catalyst and water to obtain a mixed solution A; mixing a phenol source, melamine and water to obtain a mixed solution B; 2) adding the mixed solution A into a reaction kettle, and then adding the mixed solution B into the mixed solution A drop by drop under stirring and heating; 3) after the dropwise addition is completed, the reaction is carried out under temperature rising, and after the reaction is completed, the product is obtained by cooling, discharging, filtering, washing and drying; 4) carbonizing the obtained melamine and phenolic resin to obtain a hard carbon microsphere material.

2. The production method according to claim 1, characterized by, The aldehyde source is one or more of formaldehyde, acetaldehyde, glutaraldehyde and furfural; Preferably, the dispersing agent is one or more of sodium dodecyl benzene sulfonate, sodium lignosulfonate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether (AEO), polyoxyethylene polyoxypropylene block copolymer and polyoxyethylene castor oil ester (Tween series); Preferably, the phenol source is one or more of m-dihydroxybenzene, m-trihydroxybenzene, p-dihydroxybenzene, o-dihydroxybenzene, p-aminophenol, m-aminophenol and o-aminophenol; Preferably, the catalyst is one or more of triethanolamine, ammonia, sodium hydroxide, potassium hydroxide and sodium carbonate.

3. The production method according to claim 2, characterized by, The molar ratio of the aldehyde source:phenol source:melamine in step 1) is 1.5-3:1:0.3-0.7, and more preferably 1.8-2.2:1:0.4-0.

6. Preferably, the mass ratio of the catalyst to the phenol source is 1-10:100, and preferably 3-7:

100. Preferably, the mass ratio of the dispersing agent to the phenol source is 1-20:100, and preferably 5-10:

100. More preferably, the solid content of the mixed solution A and the mixed solution B is adjusted to 10wt%-40wt%, and preferably 20wt%-30wt% by water.

4. The production method according to any one of claims 1 to 3, characterized by, In step 2), the stirring speed is 300-800 rpm, and the temperature is 50-80℃. Preferably, after heating and stirring for 30-90 min, the mixed solution B is added into the mixed solution A drop by drop, and the dropwise addition speed is 30-90 drops / min.

5. The method of any one of claims 1-3, wherein, In step 3), the temperature of the reaction kettle is raised to 60-90℃, and the reaction is carried out for 1-8 h. Preferably, in step 4), the carbonization process is as follows: the temperature is raised to 1000-1600℃ at a temperature rising rate of 2-10℃ / min, and the temperature is kept for 2-8 h to obtain the hard carbon microsphere material.

6. The production method according to claim 5, wherein In the carbonization process, the calcination must be carried out in an inert gas atmosphere, and preferably in a nitrogen, argon or helium atmosphere.

7. The hard carbon microsphere based on melamine and phenolic resin prepared by the preparation method of any one of claims 1-6.

8. The use of the melamine and phenolic composite resin-based hard carbon microspheres prepared by the preparation method of any one of claims 1-6 in the negative electrode of a sodium ion battery, characterized in that The hard carbon microsphere based on melamine and phenolic resin is prepared by mixing the hard carbon microsphere with a conductive agent and a binder, and then coating the mixture on a current collector to obtain a battery negative electrode sheet containing the hard carbon microsphere based on melamine and phenolic resin.

9. A negative electrode sheet of a sodium-ion battery, characterized by The negative electrode sheet comprises a current collector, a conductive additive, a binder and a hard carbon negative electrode material; and the hard carbon negative electrode material is the hard carbon microsphere based on melamine and phenolic resin prepared by the preparation method of any one of claims 1-6.

10. A sodium-ion battery, characterized in that The negative electrode sheet of the sodium ion battery of claim 9.

Citation Information

Patent Citations

  • Modified resin-based nitrogen-containing hard carbon material as well as preparation method and application thereof

    CN119284876A

  • High-rate and high-capacity resin-based hard carbon material as well as preparation method and application thereof

    CN119430132A